2020
DOI: 10.3390/pharmaceutics12020188
|View full text |Cite
|
Sign up to set email alerts
|

A Proof-of-Concept Study on the Therapeutic Potential of Au Nanoparticles Radiolabeled with the Alpha-Emitter Actinium-225

Abstract: Actinium-225 (225Ac) is receiving increased attention for its application in targeted radionuclide therapy, due to the short range of its emitted alpha particles in conjunction with their high linear energy transfer, which lead to the eradication of tumor cells while sparing neighboring healthy tissue. The objective of our study was the evaluation of a gold nanoparticle radiolabeled with 225Ac as an injectable radiopharmaceutical form of brachytherapy for local radiation treatment of cancer. Au@TADOTAGA was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…After a simple wash with metabisulfite, the retention of 211 AtCl@US-tubes was 60.7%. The overall labelling yield of the 211 AtCl@US-tubes was comparable to the other elaborated astatination methods [48][49][50][51][52]. An important feature of functionalised SWNTs as drug carriers is their rapid clearance via renal glomerular filtration, despite their large molecular weights [112].…”
Section: Astatine-211mentioning
confidence: 86%
See 3 more Smart Citations
“…After a simple wash with metabisulfite, the retention of 211 AtCl@US-tubes was 60.7%. The overall labelling yield of the 211 AtCl@US-tubes was comparable to the other elaborated astatination methods [48][49][50][51][52]. An important feature of functionalised SWNTs as drug carriers is their rapid clearance via renal glomerular filtration, despite their large molecular weights [112].…”
Section: Astatine-211mentioning
confidence: 86%
“…In another work proposed by Salvanou et al, 225 Ac radionuclide was conjugated to 2-3 nm gold nanoparticles via a DOTA-derivative chelator (TADOTAGA) for local radiation treatment of cancer ( Figure 5) [52]. Radiochemical yield assessed by ITLC was ~86%.…”
Section: Actinum-225mentioning
confidence: 98%
See 2 more Smart Citations
“…Bouziotis et al have reported on the synthesis of AuNPs functionalized with a thioctic acid-modified DOTAGA and radiolabeled with 225 Ac. The resulting 225 Ac-labeled AuNPs were evaluated as an injectable radiopharmaceutical form of brachytherapy for local radiation cancer treatment, using cellular and animal models of glioblastoma multiforme [133]. In vitro radiocytotoxicity studies in glioblastoma multiforme U87MG cells showed a significant cell death upon exposure to the radiolabeled AuNPs.…”
Section: Actinium-225mentioning
confidence: 99%